Evaluating the "return on patient engagement initiatives" in medicines research and development: A literature review - Lidewij Eva Vat; Teresa Finlay; Tjerk Jan Schuitmaker‐Warnaar; Nick Fahy; Paul Robinson; Mathieu Boudes; Ana Diaz; Elisa Ferrer; Virginie Hivert; Gabor Purman; Marie‐Laure Kürzinger; Robert A. Kroes; et al. (Wiley, 2020)
Abstract Background Showing how engagement adds value for all stakeholders can be an effective motivator for broader implementation of patient engagement. However, it is unclear what methods can best be used to evaluate patient engagement. This paper is focused on ways to evaluate patient engagement at three decision‐making points in the medicines research and development process: research priority setting, clinical trial design and early dialogues with regulators and health technology assessment bodies. Objective Our aim was to review the literature on monitoring and evaluation of patient engagement, with a focus on indicators and methods. Search strategy and inclusion criteria We undertook a scoping literature review using a systematic search, including academic and grey literature with a focus on evaluation approaches or outcomes associated with patient engagement. No date limits were applied other than a cut‐off of publications after July 2018. Data extraction and synthesis Data were extracted from 91 publications, coded and thematically analysed. Main results A total of 18 benefits and 5 costs of patient engagement were identified, mapped with 28 possible indicators for their evaluation. Several quantitative and qualitative methods were found for the evaluation of benefits and costs of patient engagement. Discussion and conclusions Currently available indicators and methods are of some use in measuring impact but are not sufficient to understand the pathway to impact, nor whether interaction between researchers and patients leads to change. We suggest that the impacts of patient engagement can best be determined not by applying single indicators, but a coherent set of measures.